Analisis pendapatan UMKM abon ikan tuna di Kelurahan Lappa - Nursinar, Nursinar; Rahmianti, Sri; Ramadani, Wahyu; Sari, Nur Amalia; Hidayat, Muh. Taufik; Astaman, Putra (Lembaga Penelitian, Pengembangan, Pemberdayaan Potensi Indonesia, 2024)
Indonesian fishery products in processed and fresh form are increasingly in demand in domestic and foreign markets. But one of the obstacles that occurs in fresh fish is that it is easily spoiled. Therefore, people try to process fresh fish into a product to minimize these obstacles, one of which is processing it into shredded fish. UMKM Pandawa Lima in Lappa Village is a business or business engaged in the food sector, one of its products is shredded tuna. The purpose of this study is to analyze the income of the shredded tuna fish business in Lappa Village. The research method used is descriptive qualitative research method. The analysis technique used is income analysis. The results showed that UMKM Pandawa Lima processed tuna fish into a product, namely shredded tuna fish and provided an income of Rp 1,968,000 in two production processes for one month.